Evaluation of rat pancreatic islets damage after siRNA microporation - Veronika Tomsovska; Ivan Leontovyc; Klara Zacharovova; Eva Fabryova; Tomas Koblas; Zuzana Berkova; Jan Kriz (PLoS ONE, 2026)
Small interfering RNA (siRNA) can be used for the temporary inhibition of gene expression, and one possible delivery method is microporation. In this study, we evaluated whether microporation is a suitable technique for the transfection of pancreatic islets and whether the selected siRNA is recognized by islet cells as foreign, potentially triggering an inflammatory or cytotoxic response. Rat islets were transfected with siRNA by microporation 24 hours after isolation. Another 24 hours post-transfection, the islets were assessed for viability, function, and the expression of inflammatory markers. Microporation induced mild but, in some assays, statistically significant stress. Flow cytometry revealed 9.94% dead cells in the negative control, 16.33% in islets microporated without siRNA, and 14.50% in islets microporated with siRNA. These results were confirmed by live/dead staining using Propidium iodide and Acridine orange. In contrast, caspase 3/7 staining, insulin secretion assays, and qRT-PCR analysis of inflammatory markers showed no statistically significant differences between the negative control and microporated groups. In addition, there were no significant differences in any of the assays between islets microporated with or without siRNA, or between the siRNA-only group and the negative control. These findings indicate that the selected siRNA is non-toxic to pancreatic islets and does not elicit an inflammatory response. Although microporation induces mild cellular stress and increased cell death, it may still be considered as a possible method for the transfection of pancreatic islets.